A prospective study of patients with refractory angina: outcomes and the role of high‐sensitivity troponin T. Issue 1 (18th October 2016) - Poppi, Nilson T.; Gowdak, Luís H.W.; Dourado, Luciana O.C.; Adam, Eduardo L.; Leite, Thiago N.P.; Mioto, Bruno M.; Krieger, José E.; César, Luiz A.M.; Pereira, Alexandre C.
Abstract : Background: The predictors of cardiovascular events in patients with chronic refractory angina are limited. High‐sensitivity cardiac troponin T (hs‐cTnT) assays are biomarkers that may be used to determine the prognosis of patients with stable coronary artery disease. Hypothesis: Hs‐cTnT is a predictor of death and nonfatal myocardial infarction (MI) in patients with refractory angina. Methods: We prospectively enrolled 117 consecutive patients in this study. A heart team ruled out myocardial revascularization feasibility after assessing recent coronary angiograms; evidence of myocardial ischemia served as an inclusion criterion. Optimal medical therapy was encouraged via outpatient visits every 6 months; plasma hs‐cTnT levels were determined at baseline. The primary endpoint was the composite incidence of death and nonfatal MI. Results: During a median follow‐up period of 28.0 months (interquartile range, 18.0–47.5 months), an estimated 28.0‐month cumulative event rate of 13.4% was determined via the Kaplan‐Meier method. Univariate predictors of the composite endpoint were hs‐cTnT levels and LV dysfunction. Following a multivariate analysis, only hs‐cTnT was independently associated with the events in question, either as a continuous variable (hazard ratio per unit increase in the natural logarithm: 2.83, 95% confidence interval: 1.62‐4.92, P < 0.001) or as a categorical variable (hazard ratio for concentrations above the 99th percentile: 5.14, 95% confidence interval: 2.05‐12.91, P < 0.001). Conclusions: In patients with chronic refractory angina, plasma concentration of hs‐cTnT is the strongest predictor of death and nonfatal MI. Notably, none of the outcomes in question occurred in patients with baseline plasma levels <5.0 ng/L.